Olympic Games (Beijing) analysis: the performance key - Delaš Kalinski, S.; Padulo, J.; Atikovic, A.; Milic, M.; Jelaska, I. (Acta Kinesiologica, 2016)
Despite the fact that they predominantly qualified as All-Around competitors for the Olympic Games in Beijing (OG2012), only about 61% of gymnasts competed All-Around in the Qualifying competition (C-I), while others competed on some or only on one apparatus. The smallest percentage of gymnasts competed the vault (70%); the apparatus on which the lowest value of Difficulty Score (DS=5.35), the highest value of the Execution Score (ES=8.43) and finally the highest Final Score (FS=14.03) were determined, as compared to other apparatuses. Approximately 82% competitors competed in Uneven Bars, Balance Beam and Floor. Although these were the world's best gymnasts, significant differences were determined in almost all DS, ES and FS (of all apparatuses) between differently ranked All-Around competitors of the C-I competition at the OG2012. These results are probably the consequence of tactics, but also the objectives of different gymnasts related to the results at the Olympic Games. The selection of appropriate tactics is the key in extending relatively short career of elite female gymnasts.